Improved Corn Yields When Humic Acid Extracted from Composted Manure Is Applied to Acid Soils with Phosphorus Fertilizer - Benito H. Purwanto; Putri Wulandari; Endang Sulistyaningsih; Sri N. H. Utami; Suci Handayani (Applied and Environmental Soil Science)
Most corn planted on tropical acidic soils suffers substantial yield loss caused by low crop phosphorus (P) uptake. Humic acid is recommended to increase crop P uptake since it is capable of competing with P to be bound to soil adsorption complexes. Humic acid extracted from composted manure (MHA) is a good alternative to humic acid because it is more reactive and has a higher complexation ability compared with leonardite. Therefore, the effectiveness of soil-applied MHA combined with P was evaluated to improve corn yields in acidic soils from the aspect of crop nutrient uptake efficiency and crop physiological performance. Two high-yielding corn cultivars that are highly accepted by Indonesian farmers and resistant to downy mildew disease were subjected to five different types of MHA and P combinations. The amount of P fertilizer was equivalent to 120 mg P2O5 kg−1 soil. The H10P1 produced the most significant result p<0.05 in terms of total crop dry weight, grain dry weight, and corn yield. The highest efficiency for P uptake in the leaves and grains was found with H10P1 and H5P1, respectively. Although chlorophyll content was not substantially improved, the stomatal apertures 7 weeks after planting (WAP) were significantly increased p<0.05 with H10P1 and H15P1. The photosynthetic rate and nitrate reductase (NR) activity at 10 WAP were significantly increased p<0.05 with H5P1 and H10P1, respectively. The results clearly indicated significant increases in the efficiency of crop P uptake and physiological performance for stomatal aperture, photosynthetic rate, and NR activity can highly contribute to higher corn yields.